2021
DOI: 10.1371/journal.pone.0248705
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mobile technology use and mHealth acceptance among HIV-positive men who have sex with men and transgender women in Malaysia

Abstract: Background Mobile health (mHealth) can be beneficial in monitoring the complex healthcare regimen for people with HIV that includes adhering to medication and refraining from risky practices such as unsafe sex and injection drug use. Not only is mHealth often implemented without appropriate feasibility and acceptability research, but there is limited mHealth research among key HIV-positive populations such as men who have sex with men (MSM) and transgender women (TGW). Methods This study assessed access to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…For example, over half of our participants were university graduates, compared with only one-sixth among the general adult population in Malaysia [ 72 ]. Men who have sex with men in Malaysia’s capital, however, are typically more educated, which perhaps makes the sample more representative of urban men who have sex with men in Malaysia; our findings on participants’ educational status are consistent with previous studies conducted among men who have sex with men in the region [ 49 , 71 ]. The educational level of our sample may explain the high level of interest in mHealth and the acceptability of mHealth interventions, as a higher level of education likely facilitates greater technology literacy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, over half of our participants were university graduates, compared with only one-sixth among the general adult population in Malaysia [ 72 ]. Men who have sex with men in Malaysia’s capital, however, are typically more educated, which perhaps makes the sample more representative of urban men who have sex with men in Malaysia; our findings on participants’ educational status are consistent with previous studies conducted among men who have sex with men in the region [ 49 , 71 ]. The educational level of our sample may explain the high level of interest in mHealth and the acceptability of mHealth interventions, as a higher level of education likely facilitates greater technology literacy.…”
Section: Discussionsupporting
confidence: 89%
“…While this study focused on HIV prevention behavior, knowledge, and access to services among HIV-negative Malaysian men who have sex with men, mHealth-based health intervention strategies can potentially also play an important role among HIV-positive men who have sex with men, for instance, by encouraging adherence to antiretroviral therapy and increasing retention in the HIV-care cascade [ 70 ]. High rates of mHealth acceptability have been reported in HIV-positive men who have sex with men and transgender women in Malaysia, for receiving HIV-related and sexual health information, assessing sexual and health behaviors, and receiving reminders to take HIV medications [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…(4, 6) These factors along with a lack of trust in the health care system were echoed in the result of similar studies involving transgender women from within the country (2, 6, 45)and other parts of the globe. (46-49)…”
Section: Discussionmentioning
confidence: 99%
“…Laws and policies that are discriminatory and punitive are also believed to be responsible for pushing this community away from health care services and undermining public health efforts (4,6). These factors along with a lack of trust in the health care system were echoed in the result of similar studies involving transgender women from within the country(2,6,45)and other parts of the globe (46)(47)(48)(49). The barriers and facilitators to safe sexual practices particular in relation to oral transmission of STIs were also explored.…”
mentioning
confidence: 99%
“…A recent survey of young MSM between the ages of 18 and 24 years found that approximately 70% were willing to participate in a web-based or mobile HIV prevention program, whereas only 1% would attend in-person programs exclusively [ 33 ]. As the access to and use of digital technologies do not appear to differ by mental health burden or HIV risk [ 42 , 43 ], mHealth may be a particularly attractive option for engaging underrepresented groups in settings where services are scarce.…”
Section: Introductionmentioning
confidence: 99%